Terapi Akupresur Sebagai Evidance Based Nursing Untuk Mengurangi Nyeri Dada Pada Pasien Sindrome Koroner Akut - kambu, irwan (Journal of Health Education and Literacy, 2020)
Coronary heart disease is clinically characterized by chest pain due to a blockage in the coronary arteries. Acupressure is part of complementary therapy that is able to increase endorphin levels to stimulate pain reduction. The implementation of evidence based nursing acupressure was given to 8 patients with a purposive sampling technique. The application instrument uses a visual analog pain scale rating scale. The application of acupressure was given for 20 minutes at the L14 acupressure point with a pain scale of 0 to 5. The results of the 8 samples given acupressure all patients experienced a decrease in pain scale. Emphasis or touch on the acupressure point can increase blood and systemic endorphin levels. Endorphins are the body's opiates naturally produced by the pituitary gland which are useful for reducing pain, affecting memory and mood which will then relax. Acupressure therapy has been proven to reduce pain so it is useful to apply to acute coronary syndrome patients with chest pain.